Post-traumatic growth 2.5 years after the 2011 Joplin, Missouri tornado. Issue 1 (1st January 2018) - First, Jennifer; First, Nathan; Stevens, Jordan; Mieseler, Vicky; Houston, J. Brian
ABSTRACT: In 2011 a major tornado struck Joplin, Missouri, killing 158 and injuring 1, 150 individuals. Approximately 2.5 years after this disaster, an online survey of Joplin adult residents ( N  = 438) was conducted to examine the relationship between disaster experience, post-traumatic stress (PTS) symptoms, communication with family, friends, and neighbors, and post-traumatic growth (PTG). Results indicate that more tornado exposure and tornado PTS symptoms were related to more PTG. In addition, engaging in more communication about the tornado with family, friends, and neighbors was related to more perceived PTG. Implications for social work practice in long-term post-disaster communities include building upon areas of growth and promoting positive interpersonal connections among survivors.